Integration of Hindu Values into Islamic Education System to Foster Tolerant Living (a Case Study at Bali Bina Insani Islamic Boarding School, Indonesia) - Fannani, Bakhruddin; Ma'arif , A. Samsul; Kholish, Moh Anas (Institut Agama Islam Yasni Bungo, 2024)
This article analyzes the integration of local Hindu cultural values into an Islamic education system in Bali, Indonesia. To collect the data, the researchers adopted observation, interview, and document analysis. After the data were collected, the researchers analyzed them in the light of social construction theory. The results showed that the integration could be explained well from the perspective of social construction. It started with the construction of the integration concept by the founder of the school. The moment of externalization started with the sharing of the concept. Policies on teacher recruitment, curriculum, and social disciplines would have supported the integration. Hindu teachers were recruited to teach at the Islamic school. Some subjects were enriched with points supporting the integration and a set of social disciplines was indoctrinated to the students. This objectivation moment then produced the internationalization of the concepts by the members of the school. Finally, the whole school members could accept and interact with people of other religions in a tolerant manner. The integration itself proved not only that social construction could be done in the education field, but it also gave an example of how to foster tolerance in a country of multi-religion through a multicultural education approach. This was where the research got its significance, i.e. showing the model of education suitable for multi-religious countries to foster tolerant and peaceful living.